Molecular transport properties of ZIF-8 thin films in aqueous environments: The critical role of intergrain mesoporosity as diffusional pathway - Tuninetti, Jimena Soledad (2016)
We report here the first use of electrochemical tools to quantify molecular transport from aqueous solutions into ZIF-8 MOF thin films. Our experimental findings reveal that molecular transport through ZIF-8 films in aqueous environments is purely dominated by solvent-filled intergrain mesoporosity and exhibits two well-defined transport regimes.